Lovesick Ellie. 10 - Fujimomo (Kodansha USA, 2023)
"#BestInShow Ohmi is a finalist in Japan's Top High School Boy Contest, instantly becoming an online sensation! As his devoted girlfriend, Ellie supports him all the way, both publicly and in private. But the girls in his fanbase are obsessed--They want him all to themselves! Meanwhile, Sara's on the brink of admitting her love for Reo, but there's a new player on the scene. Ellie supports her friend, being an advocate of love for all! But can she take her own advice and believe that Ohmi is committed to her?"--page [4] of cover.